Chemical Fingerprint Analysis and Ultra-Performance Liquid Chromatography Quadrupole Time-of-Flight Mass Spectrometry-Based Metabolomics Study of the Protective Effect of Buxue Yimu Granule in Medical-Induced Incomplete Abortion Rats - Zhang, Yan; Li, Wei; Chen, Ting-Ting; Yang, Yong; Wu, Meng-Yao; Luo, Jie-Ying; Gong, Yun; Zou, Liang (Frontiers in Pharmacology, 2020)
Medical abortion is a common method to terminate an early pregnancy and often causes serious complications such as abnormal uterine bleeding and endometritis. Buxue Yimu granule (BYG) is a well-known traditional Chinese medicine prescription composed of five kinds of drugs and is widely used in gynecology and obstetrics. The aim of the present study was to establish the quality standard of BYG and investigate its protective effect on incomplete abortion. The chemical fingerprint of BYG was established by high performance liquid chromatography (HPLC). The major compounds of BYG were determined by ultra-performance liquid chromatography with triple quadrupole mass spectrometry. An incomplete abortion rat model was induced by intragastric administration of mifepristone (8.3 mg·kg−1) combined with misoprostol (100.0 μg·kg−1) during early pregnancy. The serum levels of human chorionic gonadotrophin (HCG), estradiol (E2), and progesterone (PG) were determined. The serum endogenous metabolites were analyzed by ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS). Multivariate analysis, including partial least squares discriminant analysis (PLS-DA) and orthogonal partial least squares discriminant analysis (OPLS-DA), was employed to analyze the metabolic profiles, and MetaboAnalyst was used to investigate the metabolic pathways. Furthermore, hematoxylin-eosin staining (HE) was used to evaluate the histopathological changes in uterine tissue. The expression levels of VEGFA and NF-κB were detected by immunohistochemistry. The results indicated that HPLC fingerprint analysis can be successfully used to assess the quality of BYG. The medical-induced incomplete abortion rats were clearly separated from control rats, and the biochemical changes were gradually restored to normal after administration of BYG. Moreover, 19 potential biomarkers, including N-lactoylleucine, 2-piperidinone, isobutyryl-l-carnitine, eicosapentaenoylcholine, LysoPC(14:0), LysoPC(20:5), physagulin C, LysoPC(18:3), leukotriene D5, deoxycholic acid 3-glucuronide, glycine, pregnanediol 3-O-glucuronide, LysoPC(18:2), LysoPC(17:0/0:0), N-acetyl-leukotriene E4, LysoPC(18:0), platelet-activating factor, LysoPA(24:1), and LysoPC(18:1), which were mainly related to the amino acids metabolism, lipids metabolism, and bile acid biosynthesis, were identified. Consequently, BYG exerts a potential protective role in the intervention of incomplete abortion by anti-inflammatory, promote endometrial repair, and regulate the metabolic disorders.